The clinical importance of metagenomic next-generation sequencing in detecting disease-causing microorganisms in cases of sepsis acquired in the community or hospital setting - Zhang, Dan; Li, Xingxing; Wang, Yu; Zhao, Yong; Zhang, Hong (Frontiers in Microbiology, 2024)
Although metagenomic next-generation sequencing (mNGS) is commonly used for diagnosing infectious diseases, clinicians face limited options due to the high costs that are not covered by basic medical insurance. The goal of this research is to challenge this bias through a thorough examination and evaluation of the clinical importance of mNGS in precisely identifying pathogenic microorganisms in cases of sepsis acquired in the community or in hospitals.A retrospective observational study took place at a tertiary teaching hospital in China from January to December 2021.Data on 308 sepsis patients were collected, and the performance of etiological examination was compared between mNGS and traditional culture method.229 cases were observed in the community-acquired sepsis(CAS)group and 79 cases in the hospital-acquired sepsis (HAS) group. In comparison with conventional culture, mNGS showed a significantly higher rate of positivity in both the CAS group (88.21% vs. 25.76%, adj.P<0.001) and the HAS group (87.34% vs. 44.30%, adj.P<0.001), particularly across various infection sites and specimens, which were not influenced by factors like antibiotic exposure or the timing and frequency of mNGS technology.Sepsis pathogens detected by mNGS were broad, especially viruses, Mycobacterium tuberculosis, and atypical pathogens, with mixed pathogens being common, particularly bacterial-viral co-detection. Based on the optimization of antimicrobial therapy using mNGS, 58 patients underwent antibiotic de-escalation, 2 patients were switched to antiviral therapy, and 14 patients initiated treatment for tuberculosis, resulting in a reduction in antibiotic overuse but without significant impact on sepsis prognosis. The HAS group exhibited a critical condition, poor prognosis, high medical expenses, and variations in etiology, yet the mNGS results did not result in increased medical costs for either group.mNGS demonstrates efficacy in identifying multiple pathogens responsible for sepsis, with mixed pathogens of bacteria and viruses being prevalent. Variability in microbiological profiles among different infection setting underscores the importance of clinical vigilance. Therefore, the adoption of mNGS for microbiological diagnosis of sepsis warrants acknowledgment and promotion.